Value of Autoantibody Expression During Long-Term Follow-Up in Paediatric ALL Patients After Allogeneic Haematopoietic Stem Cell Transplantation - Lawitschka, Anita; Ronceray, Leila; Bauer, Dorothea; Rittenschober, Michael; Zubarovskaya, Natalia; Geyeregger, Rene; Pickl, Winfried F.; Kuzmina, Zoya (Frontiers in Pediatrics, 2021)
Chronic graft-versus-host disease (cGvHD) following HSCT shares many similarities with de novo autoimmune disorders, being associated with the presence of autoantibodies. However, data on the implication of autoantibodies in paediatric HSCT recipients are scarce. In this single-centre study of paediatric patients with acute lymphoblastic leukaemia (ALL) surviving longer than 3 months, our objectives were to evaluate autoantibody expression and investigate the correlation with cGvHD and immune reconstitution using serially monitored parameters. We investigated circulating autoantibodies together with cellular and humoral parameters (including major T- and B-cell subsets, natural killer [NK] cells, and immunoglobulin levels) in 440 samples from 74 patients serially during long-term follow-up of median 8 years. Autoantibodies were detected in 65% of patients. Neither the expression of autoantibodies nor the occurrence of cGvHD correlated with significantly worse OS or relapse rate. there was no significant association between autoantibody profiles and the incidence, overall severity or organ involvement of cGvHD. Patients with autoantibodies showed significantly better immune reconstitution, with overall higher numbers of T cells, B cells and serum immunoglobulins. In autoantibody-positive patients with cGvHD, autoantibody production positively correlated with the expansion of CD56+ NK cells (p=0.023) and with signs of B-cell perturbation, such as higher CD21low B cells (p=0.044) When comparing immune parameters of the large proportion of survivors (89%) to non-survivors (11%), data revealed normalization within the B-cell compartment of survivors: increased of CD27+ memory B cells (p=0.05), class-switched CD27+IgD- B cells (p<0.0001) and immunoglobulin G4 (40.9 vs 19.4 mg/dL, respectively; p<0.0001). Overall mortality was significantly associated with an elevated proportion of CD21low B cells (p=0.039) and CD56+ NK cells (p=0.019). In multivariate analysis, better OS was significantly associated with lower numbers of CD56+ NK cells (p=0.041) and higher numbers of CD27+ memory B cells (p=0.014). Our data shows that autoantibody profiles are not suitable biomarkers for diagnosing cGvHD in children or for predicting cGvHD severity, disease course and outcome. These findings confirm published results and suggest that candidate B cell subpopulations may serve as a surrogate measure for characterization of cGvHD in paediatric HSCT for malignant diseases, and warrants confirmation in larger, multicentre studies.